Algoritmo das projeções sucessivas aplicado à seleção de variáveis em regressão PLS - Gomes, Adriano de Araújo (2012)
Spectroscopy techniques combined with multivariate calibration have allowed the development of methods for analyte determinations (or other properties) in complex matrices. In this context, it can be mentioned the determinations that uses models based on PLS (Partial Least Square) regression, which is well established and consolidated in literature. Is spite of efficiency of PLS models obtained from full spectrum, some papers reported in literature show that a variable selection may improve the predictive ability of the PLS models. In the present work, it was developed an algorithm, in Matlab@, that employs the SPA (Successive Projection Algorithm), originally proposed for MLR (Multiple Linear Regression), in order to improve the predictive ability of interval PLS models. The proposed algorithm, termed iSPA-PLS, was evaluated in three case studies, namely: (i) simultaneous determination of three artificial colorants by UV-VIS spectrometry, (ii) quantification of protein contents in wheat using NIR spectrometry, and (iii) quality determination of samples of beer extract using NIR spectrometry too. The performance of iSPA-PLS was compared to the following well-established algorithms and methods: GA-PLS, PLS-Jack-Knife, iPLS e siPLS. In all applications, the results show that the iSPA-PLS presented some advantageous when compared to other algorithms used for comparison. The main advantageous include the smallest errors of prediction and the capacity of selecting a smaller number of PLS factors.